Pengaruh Tarif Pajak, Tingkat Penghasilan, Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak UMKM - Erlita Widiya Putri; Sri Trisnaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The biggest source of income in Indonesia comes from the tax sector. The government has begun to intensively optimize sectors that have the potential to contribute to tax revenues, one of which is MSME. Until now, MSME taxpayer compliance is still considered very low. The purpose of this study was to examine the effect of tax rates, income levels, and taxpayer awareness on MSME taxpayer compliance. This research is a type of quantitative research. The data used are primary data using multiple linear regression analysis and processed using the SPSS application. Data collection was carried out by distributing questionnaires directly to each respondent. The sampling technique used was purposive sampling. The sample criteria in this study are MSMEs that have NPWP. A total of 33 MSME actors in the Tegalsari District met the criteria and were used as research samples. The results of this study indicate that income levels and taxpayer awareness have a positive and significant effect on MSME taxpayer compliance, while tax rates have a negative and insignificant effect on MSME taxpayer compliance. Keywords: Taxpayer Awareness, Tax Rates, Income Level